1984. Implementation of an integrated infectious disease and substance use disorder team for the treatment of severe injection-related infections. (15th December 2022) - Seo, Grace; Hervera, Belén; Bartholomew, Tyler; Chueng, Teresa A; Chueng, Teresa A; Suarez, Edward; Forrest, David; Hernandez, Salma; Rodriguez, Allan; Tookes, Hansel; Doblecki-Lewis, Susanne; Serota, David P
Abstract: Background: Hospitalizations for severe injection drug use-related infections (SIRIs) are characterized by high costs, frequent patient-directed discharge, and high readmission rates. Beyond the health system impacts, these admissions can be traumatizing to people who inject drugs (PWID), who often receive inadequate treatment for their substance use disorders (SUD). The Jackson SIRI team was developed as an integrated infectious disease/SUD treatment team for patients hospitalized at a public safety-net hospital in Miami, Florida in 2020. In order to facilitate implementation of this team, we conducted a qualitative study of patients and providers to identify barriers and facilitators to the team's success. Methods: Participants were patients with history of SIRIs (n=7) at the Jackson Memorial Hospital (JMH) and healthcare providers (HCPs) (n=8) at JMH. Semi-structured qualitative interviews were performed with a guide created using the Consolidated Framework for Implementation Science (CFIR). Interviews were transcribed and double coded by study team members using determinants adapted from the CFIR. Results: Key barriers to SIRI team success included: 1) complexity of SIRI and SUD care requiring multidisciplinary teams and resources; 2) lack of resources for PWID experiencing homelessness, financial insecurity, and uninsured status; 3) stigma and lack of knowledge around addiction and medications for SUD; and 4) suspected understaffing and underfunding for the team. Facilitators of team success included: 1) holistic, integrated care being more efficient and effective than fragmented care; 2) the team's advocacy for PWID as a means of institutional culture change; 3) provision of close post-hospital follow-up for an often-abandoned population; 4) non-judgmental, harm reduction-oriented approach; and 5) addressing diverse needs such as housing, insurance, and psychological wellbeing. Conclusion: Integration of infectious disease and substance use disorder treatment is a promising approach to managing patients with SIRIs; however, success depends on institutional buy-in, holistic care beyond the medical domain, and an ethos rooted in harm reduction. Disclosures: Susanne Doblecki-Lewis, MD, MSPH, Gilead Sciences: Grant/Research Support.